2005
DOI: 10.1186/ar1489
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 in osteoarthritic chondrocytes triggers nitric oxide production and upregulates collagenase production

Abstract: The mechanism of endothelin-1 (ET-1)-induced nitric oxide (NO) production, MMP-1 production and MMP-13 production was investigated in human osteoarthritis chondrocytes. The cells were isolated from human articular cartilage obtained at surgery and were cultured in the absence or presence of ET-1 with or without inhibitors of protein kinase or LY83583 (an inhibitor of soluble guanylate cyclase and of cGMP). MMP-1, MMP-13 and NO levels were then measured by ELISA and Griess reaction, respectively. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…We found that ET-1 did not act on IVD degeneration through induction of apoptosis. Others have reported similar results of ET-1 on articular chondrocytes without apoptosis [13].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…We found that ET-1 did not act on IVD degeneration through induction of apoptosis. Others have reported similar results of ET-1 on articular chondrocytes without apoptosis [13].…”
Section: Discussionsupporting
confidence: 59%
“…ET-1 was firstly discovered in aortic endothelial cells, and has since been found to be produced by many cell types [12]. Interestingly, ET-1 is not only a potent vasoconstrictor, but is also associated with inflammation in degenerative diseases mainly via endothelin receptor type A. ET-1 causes excessive production of NO, which is generated following increases in inducible nitric oxide synthase (NOS) levels [13][15]. In addition, ET-1 promotes MMP-1 and MMP-13 synthesis and activation in osteoarthritis cartilage [16].…”
Section: Introductionmentioning
confidence: 99%
“…A previous report by Li and colleagues has shown that TGFB induces activation of AKT in precartilaginous stem cells, and inhibition of AKT activity suppresses TGFB-induced expression of SOX9 , AGN , and COL2 [ 50 ], indicating the crucial role of AKT signaling in chondrogenesis. In addition to the AKT signaling pathway, other pathways, such as the mitogen activated-protein kinase pathway [ 26 , 27 ] or the Ca 2+ /calmodulin-dependent protein kinase cascade [ 28 ], activated by ET1, may also be involved in the regulation of hMSC activities induced by ECs. However, investigation into how ECs regulate hMSCs through other signaling pathways is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…ET1 binds to endothelin receptor type A or B on the cell surface to activate downstream signaling molecules of several pathways, including mitogen activated-protein kinase [ 26 , 27 ], Ca 2+ /calmodulin-dependent protein kinase [ 28 ], protein kinase C [ 29 , 30 ], and phosphatidylinositol 3-kinase/AKT [ 31 , 32 ]. It is known that these signaling molecules play a role in regulation of MSC behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent studies have revealed that endothelin-1 is produced in OA cartilage and synovial membrane, and that it upregulates MMP expression and synthesis, as well as increasing collagen type II degradation in human cartilage [60,61].…”
Section: Endothelin-1mentioning
confidence: 99%